Bonding in molecular crystals from the local electronic pressure viewpoint. (17th April 2016) - Tsirelson, Vladimir G.; Stash, Adam I.; Tokatly, Ilya V.
ABSTRACT: The spatial distribution of the internal pressure of an electron fluid, which spontaneously arises at the formation of a molecule or a crystal, is linked to the main features of chemical bonding in molecular crystals. The local pressure is approximately expressed in terms of the experimental electron density and its derivatives using the density functional formalism and is applied to identify the bonding features in benzene, formamide and chromium hexacarbonyl. We established how the spatial regions of compression and stretching of the electron fluid in these solids reflect the typical features of chemical bonds of different types. Thus, the internal electronic pressure can serve as a bonding descriptor, which has a clear physical meaning and reveals the specific features of the variety of the chemical bonds expressing them in terms of the electron density. GRAPHICAL ABSTRACT: